#Cheers: An Examination of User-Generated Alcohol Advertising on Instagram. (28th January 2023) - Thompson, Kara; DeWolf, Darien; MacDonald-Spracklin, Rachael; Frank, Delaney; Cooper, Stephanie
Abstract: Background: Alcohol marketing is a known risk factor for youth drinking. The growth in digital marketing has generated a new form of alcohol advertisement in which brands solicit and/or share consumer-generated or user-generated content. Objectives: The current study investigates the prevalence of UGC alcohol advertising on social media and examines the content of UGC advertising to determine potential violations of current regulatory guidelines. Results: The Instagram accounts of 20 Nova Scotia breweries were monitored for the month of July 2021. User-generated content made up a substantial portion (41%) of all Instagram stories (n = 1531), and there were 321 violations of the Canadian Radio-television and Telecommunications Commission code for broadcast advertising of alcoholic beverage. Ten percent of violations encouraged consumption, 59% depicted irresponsible use, 14% appealed to youth, 14% associated alcohol with activities requiring a degree of skill or care, 2.5% associated alcohol with social or personal success. Conclusions/Importance : These findings indicate that UGC is a commonly used marketing strategy among alcohol producers and the current self-regulatory system is insufficient in preventing advertising that appeals to youth and exacerbates a culture of immoderate consumption.